2014
DOI: 10.1155/2014/583069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Pretreatments to the Seed on Seedling Emergence and Growth ofAcacia polyacantha

Abstract: Acacia polyacanthaWilld. is a multipurpose tree species prioritised as one of the agroforestry tree species in Malawi. However, its use in agroforestry practices is limited by the low seedling growth and survival at the nursery stage. A study was conducted to evaluate the seedling growth and survival ofAcacia polyacanthaas affected by different pretreatments on the seeds at Malawi College of Forestry and Wildlife nursery, Malawi. Seeds were subjected to five presowing seed treatments methods, namely, immersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 11 publications
3
30
1
Order By: Relevance
“…Mechanical and chemical scarification were more effective in rendering seeds of F. albida permeable, leading to a mean germination of up to 69.67 and 67.67 % respectively. Mechanical scarification which recorded highest germination percentage is known to break physical dormancy of hard seed coats by enhancing gases and water uptake especially in Acacia species (Missanjo et al 2014). The enhanced germination observed in the mechanical treatment could be attributed to water uptake by the quiescent dry seed, which ended up with the elongation of the embryonic axis (Botsheleng et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical and chemical scarification were more effective in rendering seeds of F. albida permeable, leading to a mean germination of up to 69.67 and 67.67 % respectively. Mechanical scarification which recorded highest germination percentage is known to break physical dormancy of hard seed coats by enhancing gases and water uptake especially in Acacia species (Missanjo et al 2014). The enhanced germination observed in the mechanical treatment could be attributed to water uptake by the quiescent dry seed, which ended up with the elongation of the embryonic axis (Botsheleng et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the best subset regression analysis was carried out to select predictor variables that explained the largest variation in tree growth rate [16,17]. When two independent variables are highly correlated the analytical procedure used automatically drops one of the predictor variables to avoid problems of collinearity (Analytical Software, 1985-2008) [13,18]. Best subset regression analysis simultaneously compares models with single variables and all their possible combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated seeds were sown on 77 stations with five seeds per station and scarified seeds were sown on 72 stations with two seeds per station in two separate rows. The stations and rows were 1.0 m apart and the planting stations were marked by aluminum stakes for easy resighting during subsequent inspections [13]. Seeds were sown in shallow holes (2 -3 cm deep) and seedling emergence (used as a proxy for seed germination) was monitored at weekly intervals during the wet (rainy) season for three years to obtain data on phased seed germination.…”
Section: Seedling Germination and Survivalmentioning
confidence: 99%
“…On the other hand, shoot/root weight ratio of seedlings of clay and mixture media were identical. The study which conducted by [5] illustrated that, the polybag size has main effects on performance of tree seedlings propagation in the nurseries. …”
Section: Seedlings Growth Assessment Of a Polycantha In Different Grmentioning
confidence: 98%
“…Root restriction is an inherent problem with container grown trees, According to [4] (Appleton & Whitcomb, 1983) plants grown in standard plastic containers for too long often have deformed roots that are kinked or grow along the sides or bottom of the root ball. Results from literature of [5] revealed that tree seedlings raised in poly bags were taller than those from root trainers; probably because many of the poly bags grown seedlings had rooted in the nursery soil and so they were accessing additional resources not available to the root trainer-grown seedlings.in addition, [6] stated that nursery containers have been testified as one of the crucial factors that enhance the successful growth of tree seedlings. Although this provided additional resources to seedlings in bags, it also resulted in severing of roots during transplanting to the field.…”
Section: Introductionmentioning
confidence: 99%